Audit Fee Determinants for FTSE 350 Companies Listed on London Stock Exchange and Individual Big 4 Premium and Industry Specializations - Kam, Wing Lam Henry (2009)
Big 4 auditors’ premium charged by the Big 4 auditors has found to have important influence on fees due to the so-called `higher quality’. The present study examines the determinants of audit fee by focusing on individual Big 4 premium and audit industry specialization in the UK FTSE 350 market for a sample of 978 companies. The study finds no evidence of individual Big 4 premium and premium pricing among the Big 4 auditors. Industry specialization was found to be significant in the whole group but it turned out to be insignificant within the specialist industries. In contrast to the previous studies, the study finds Big 4 industry specialists charge less audit fees in the market in compared to non-industry specialists. Consistent with much precious researches, other variables including auditees’ size, non-audit services fees, number of subsidiaries, receivable to total assets, number of employees, loss dummy variable, busy season and location were all found to have significant influence on audit fees. Surprisingly, ratio of international subsidiaries to total subsidiaries and inventory to total assets were only significant within the specialist industries. Moreover, neither of the profitability measures was successful in explaining audit fees throughout the study.